Charitable giving and its persistent and transitory reactions to changes in tax incentives: Evidence from the German taxpayer panel - Timm Bönke; Clive Werdt (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
We estimate the elasticity of charitable giving with respect to price and income changes using a rich panel of income tax returns covering the period 2001 to 2006. Employing censored quantile regression and exploiting the panel structure, the advantage of our analysis is twofold: First, we derive results for different points in the underlying distribution of charitable giving and allow for giving to be heterogeneous. Thus, we do not only estimate responses of giving to prices and incomes but also where the incentives matter most. Second, we disentangle long-run responses to persistent changes in price and income from temporary reactions, consumption smoothing, or tax planning. Indeed, our results suggest that price elasticity is heterogenous across the distribution of donors and that the persistent price elasticity is close to one in absolute value at the upper and lower tail of the distribution of charitable giving.
Keywords: C31; H31; H53; 330; charitable giving; price and income elasticity; censored quantile regression; taxpayer panel; administrative data; school performance